2012
DOI: 10.1007/s00439-012-1229-4
|View full text |Cite
|
Sign up to set email alerts
|

HOXB13 is a susceptibility gene for prostate cancer: results from the International Consortium for Prostate Cancer Genetics (ICPCG)

Abstract: Prostate cancer has a strong familial component but uncovering the molecular basis for inherited susceptibility for this disease has been challenging. Recently, a rare, recurrent mutation (G84E) in HOXB13 was reported to be associated with prostate cancer risk. Confirmation and characterization of this finding is necessary to potentially translate this information to the clinic. To examine this finding in a large international sample of prostate cancer families, we genotyped this mutation and 14 other SNPs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
114
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 171 publications
(130 citation statements)
references
References 31 publications
10
114
1
5
Order By: Relevance
“…Several studies have identified a specific HOXB13 mutation in 1.4-4.6% of individuals (primarily of Northern European ancestry) meeting these criteria. [53][54][55] Identifying the basis of familial prostate cancer is ongoing, and genes found to date account for a small portion of families. However, referral may be appropriate for these families to help address concerns and provide screening recommendations.…”
Section: Familial Pancreatic Cancer (Omim 260350)mentioning
confidence: 99%
“…Several studies have identified a specific HOXB13 mutation in 1.4-4.6% of individuals (primarily of Northern European ancestry) meeting these criteria. [53][54][55] Identifying the basis of familial prostate cancer is ongoing, and genes found to date account for a small portion of families. However, referral may be appropriate for these families to help address concerns and provide screening recommendations.…”
Section: Familial Pancreatic Cancer (Omim 260350)mentioning
confidence: 99%
“…Only an index case was originally genotyped, and additional individuals were studied only to confirm segregation of the mutation. Seventy-six index individuals overlapped with those genotyped in the large multinational ICPCG study (19). To investigate the cosegregation of the G84E mutation in nonoverlapping, mutation-positive families, additional healthy and affected family members were genotyped.…”
Section: Study Subjectsmentioning
confidence: 99%
“…Fifteen of these 32 families overlapped with the ICPCG dataset (19). Cosegregation of G84E with prostate cancer in the remaining 17 families was assessed by genotyping an additional 28 healthy and 37 affected family members, for whom DNA samples were available.…”
Section: Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…While the biomedical relevance of this work is extremely high (17% of American men will get prostate cancer), the genetics are proving to be somewhat more difficult than trait mapping in dogs. However, recent studies have successfully identified candidate loci associated with susceptibility to prostate cancer in high-risk families and certain populations (Jin et al 2012;Stott-Miller et al 2012;Taioli et al 2012;Xu et al 2013).…”
Section: Challenging Cancer Geneticsmentioning
confidence: 99%